Peeled images and sectioned images from real-color volume models of foot. - Park, Jin Seo; Jung, Yong Wook (Surgical & Radiologic Anatomy, 2021)
Purpose: In all educational materials, the foot cannot be peeled from skin to the bone at constant intervals, like as real dissection. The aim of this study was to produce the peeled images which the foot structures can be peeled gradually along a skin-curved surface in real color, like a real dissection. In addition, the sectioned images of typical and atypical planes are presented in real color and high resolution. Methods: From the sectioned images of real color, foot volume models were made using Photoshop, Matlab, and MRIcroGL. Peeled images and sectioned images of the typical planes were produced from the volume models. All images were placed into the browsing software. An atypical plane could be shown in a real-time using the volume models of the foot. Results: Using the peeled images, in which the foot can be rotated at 5-degree intervals and stripped gradually at 0–30 mm depth, the foot anatomy could be learned precisely and efficiently. The sectional anatomy of the foot for radiology and orthopedic surgery could also be learned easily using the sectioned images of typical (horizontal, coronal, and sagittal) and atypical planes. Conclusion: The most significant merit of the volume models is that all outcomes can be displayed with proper colors of the body structures on any plane. By virtue of these merits, the volume models are useful for learning medical education, research, and clinical practice.